3x+5=11. 14x -6=30x+6. (x-1)(x+1)=(x+3)(x-3)
Răspunsuri la întrebare
Răspuns de
0
3x+5=11
3x=11-5
x=6:3
x=2
3x=11-5
x=6:3
x=2
Răspuns de
1
3x+5=11
3x=11-5
3x=6
x=2
14x-6=30x+6
-6-6=30x-14x
-12=16x
x=-12/16=-3/4
xla 2+x-x-1=x la 2-3x+3x-9
x la 2-1=xla2-9
3x=11-5
3x=6
x=2
14x-6=30x+6
-6-6=30x-14x
-12=16x
x=-12/16=-3/4
xla 2+x-x-1=x la 2-3x+3x-9
x la 2-1=xla2-9
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă